IMPLEMENTASI PENGAMANAN FILE DI PT. XYZ (STUDI PUSTAKA MANAJEMEN SEKURITI) - Achmad Mahardika Dwi Anda Putra Prasetio; Aldy Putra Puji Siswoko, Bagus Oktavian, Andre Satrio Trihantono, Muhammad Naufal Ramadhan, Sahrul J (BORJUIS: JURNAL OF ECONOMY, 2025)
This research analyzes the implementation of file security at PT. XYZ, is Indonesia's national energy industry which operates in the field of exploration, creation and distribution of energy resources. In facing cyber security threats such as hacker attacks, data theft and sabotage, PT. XYZ must guarantee the security of information and the integrity of files stored in their systems. This research uses qualitative methods and a literature review to evaluate the steps taken by PT. XYZ in protecting sensitive information and maintaining the trust of customers and business partners. The analysis results show that PT. XYZ has implemented several file security practices, including access control, data encryption, backup and recovery, activity monitoring, security policy settings, and security training and awareness. This implementation is expected to provide guidelines and recommendations for improving information security in the oil and gas industry sector.